The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cells9092019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Analytical Factors on MSI Test Accuracy in Mucinous Colorectal Adenocarcinoma: A Multi-Assay Concordance Study

Abstract: Immunohistochemistry (IHC) and polymerase chain reaction (PCR) and fragment separation by capillary electrophoresis represent the current clinical laboratory standard for the evaluation of microsatellite instability (MSI) status. The importance of reporting MSI status in colorectal cancer is based on its potential for guiding treatment and as a prognostic indicator. It is also used to identify patients for Lynch syndrome testing. Our aim was to evaluate pre-analytical factors, such as age of formalin-fixed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 32 publications
0
54
0
1
Order By: Relevance
“…However, evaluation and interpretation of immunohistochemical results may at times be challenging because of intra-and inter-observer variability and pre-analytical and analytical issues [1]. In this scenario, evaluation of microsatellite instability (MSI) through molecular approaches, such as polymerase chain reaction (PCR), genomic sequencing, and capillary electrophoresis, has been proposed as a valuable alternative to overcome some of the issues inherent to immunohistochemistry (IHC) [1,11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, evaluation and interpretation of immunohistochemical results may at times be challenging because of intra-and inter-observer variability and pre-analytical and analytical issues [1]. In this scenario, evaluation of microsatellite instability (MSI) through molecular approaches, such as polymerase chain reaction (PCR), genomic sequencing, and capillary electrophoresis, has been proposed as a valuable alternative to overcome some of the issues inherent to immunohistochemistry (IHC) [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the most widely adopted procedure for MSI evaluation relies on the Sanger sequencing-based Bethesda panel, which covers two mononucleotide (BAT-25 and BAT-26) and three dinucleotide (D5S346, D2S123, and D17S250) repetitions [13] or, alternatively, a panel covering five poly-A mononucleotide repeats (BAT-25, BAT-26, NR-21, NR-24, NR-27) [14]. However, recent studies have demonstrated that the fully automated PCR high-resolution melt curve analysis (Idylla TM , Biocartis, Mechelen, Belgium) [11,[15][16][17][18][19][20][21][22][23][24][25][26] and the automated microfluidic electrophoretic run chip-based assay (TapeStation 4200, Agilent Technologies, Santa Clara, CA, USA) are easier to use, faster, and less expensive than Sanger sequencing [11,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22.64% of patients in our study group had tumors with high microsatellite instability (MSI-H) (12/53, only 53 patients were tested for MSI status). Recent work showed that MSI detection of mucinous adenocarcinoma requires caution [35]. Second, it warrants close observation of the progress of the disease and the level of tumor markers after operation, and close follow-ups should be scheduled for all these patients.…”
Section: Discussionmentioning
confidence: 99%
“…DNA quality is high in blood and variable in FFPE tissue [ 17 ]. Factors that can lower DNA quality are in common with other molecular tissue tests, i.e., presence of necrosis, high infiltration of inflammatory cells, aging-related degradation, poor fixation in formalin, cauterized tissue [ 18 ]. Nonetheless, the reliability of tumor testing in diagnosing or excluding germline mutations is questionable.…”
Section: Tissue Testing Vs Whole Blood Testingmentioning
confidence: 99%